An Analysis of the Implementation Duolingo Application in Teaching English Skills in Eleventh Grade at SMA Negeri 1 Tasifeto Timur - Franti V. Manes; Rudulof J. Isu; Yanrini M. Anabokay; Rocky P. Sekoni (Jurnal Pendidikan Dirgantara, 2025)
This study examines the implementation of the Duolingo application in teaching English skills to eleventh-grade students at SMA Negeri 1 Tasifeto Timur. With the increasing integration of technology in education, this research aims to evaluate the effectiveness of Duolingo as a tool for enhancing language acquisition and engagementt among learners. Through a mixed-methods approach, the study analyzes student performance, engagement levels, and overall satisfaction with the application compared to traditional teaching methods. The results indicate a significant improvement in vocabulary retention, grammatical proficiency, and conversational skills among students utilizing Duolingo. Additionally, qualitative feedback highlights the app's user-friendly interface and gamified learning experience as motivating factors.